2016
DOI: 10.1002/smi.2703
|View full text |Cite
|
Sign up to set email alerts
|

Are We All in the Same Boat? The Role of Perceptual Distance in Organizational Health Interventions

Abstract: The study investigates how agreement between leaders' and their team's perceptions influence intervention outcomes in a leadership‐training intervention aimed at improving organizational learning. Agreement, i.e. perceptual distance was calculated for the organizational learning dimensions at baseline. Changes in the dimensions from pre‐intervention to post‐intervention were evaluated using polynomial regression analysis with response surface analysis. The general pattern of the results indicated that the orga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 45 publications
1
22
0
1
Order By: Relevance
“…This approach has also been utilized in previous studies (e.g., Koopman et al, 2019). Another option that has been used in other studies (e.g., Hasson et al, 2016) is for the supervisor to select one or a few employees and to have the relevant responses concern interactions with those individuals. With such an approach, even though it is advantageous to capture a supervisor's ratings in regard to a particular employee, there is a risk that the supervisor will only select employees with whom they have had positive interactions, which can bias the results.…”
Section: Methodological Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…This approach has also been utilized in previous studies (e.g., Koopman et al, 2019). Another option that has been used in other studies (e.g., Hasson et al, 2016) is for the supervisor to select one or a few employees and to have the relevant responses concern interactions with those individuals. With such an approach, even though it is advantageous to capture a supervisor's ratings in regard to a particular employee, there is a risk that the supervisor will only select employees with whom they have had positive interactions, which can bias the results.…”
Section: Methodological Considerationsmentioning
confidence: 99%
“…Previous research has found that the level of such congruence between how the supervisors evaluate themselves and the employees' evaluations of them can influence employees' attitudes and behaviors. This has been found in fields such as trust (Carter and Mossholder, 2015), psychological contracts (Kim et al, 2017), leadership (Atwater et al, 2009;Aarons et al, 2017;Carter et al, 2018), team interventions (Hasson et al, 2016), organizational learning (Tafvelin et al, 2017), and organizational support (Bashshur et al, 2011). Based on this, the following hypotheses were formulated: Hypothesis 3.…”
Section: The Role Of Perceptual Congruencementioning
confidence: 99%
“…The interview data were transcribed and uploaded into NVivo. Descriptive coding was applied during the first coding cycle (Hasson, von Thiele Schwarz, Nielsen, & Tafvelin, ) with a focus on the themes of design characteristics of the visualization object, the participants’ application of the visualization object (process characteristics) and the participants’ perception of impact. The data used to analyze the design characteristics included observations and photos.…”
Section: Methodsmentioning
confidence: 99%
“…Tätä tukee Hassonin ym. (30) tutkimus, jossa parempi yhteisymmärrys esimiesten ja työntekijöiden välillä organisaatiokulttuurista ennen organisatorista interventiota ennusti parempia tuloksia ja jossa oppivan organisaation kehitys oli parhainta silloin, kun organisaatiokulttuuri oli arvioitu yhte näisesti hyväksi (30). Meta-analyysi on taas osoittanut, että erilaiset organisaatiokulttuuriprofiilit ovat eri tavoin positiivisesti yhteydessä organisaation tehokkuuteen (31).…”
Section: Tutkimuksen Lähtökohdatunclassified